2017
DOI: 10.1098/rstb.2016.0266
|View full text |Cite
|
Sign up to set email alerts
|

Tumour virus epidemiology

Abstract: A viral etiology of cancer was first demonstrated in 1911 by Peyton Rous who injected cell-free filtrate from a chicken sarcoma into healthy chickens and found it induced a tumour. Since the discovery over 50 years ago of the Epstein-Barr virus as the cause of Burkitt lymphoma, seven other human viruses or groups of viruses-hepatitis B virus, hepatitis C virus, human immunodeficiency virus type 1, some human papillomaviruses, human T-cell lymphotropic virus type 1, Kaposi sarcoma-associated herpesvirus and Mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 62 publications
2
33
0
1
Order By: Relevance
“…The line of reasoning I have been developing applies only to cancers that cannot move between hosts (noninfectious cancers) and cancers that are not associated with pathogens. But approximately 15% of all human cancers worldwide are known to be caused by pathogens (Lunn, Jahnke, & Rabkin, ; Plummer et al., ), and some observers suggest the true figure may prove to be higher (Ewald & Swain Ewald, ). Pathogens are more different biochemically from healthy human cells than are human tumor cells, offering greater opportunities for selective toxicity (Ewald & Swain Ewald, , ), as well as more abundant preventive approaches to cancer (e.g., vaccination).…”
Section: Infectious and Pathogen‐associated Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…The line of reasoning I have been developing applies only to cancers that cannot move between hosts (noninfectious cancers) and cancers that are not associated with pathogens. But approximately 15% of all human cancers worldwide are known to be caused by pathogens (Lunn, Jahnke, & Rabkin, ; Plummer et al., ), and some observers suggest the true figure may prove to be higher (Ewald & Swain Ewald, ). Pathogens are more different biochemically from healthy human cells than are human tumor cells, offering greater opportunities for selective toxicity (Ewald & Swain Ewald, , ), as well as more abundant preventive approaches to cancer (e.g., vaccination).…”
Section: Infectious and Pathogen‐associated Cancersmentioning
confidence: 99%
“…Evolution in these viral populations will, in both the short and long terms, oppose both direct antiviral treatments (e.g., in response to screen‐and‐treat programs against hepatitis B and C virus infections; Plummer et al., ) and anticancer treatments. We have, however, made great strides in preventing at least some of these cancers with vaccines (human papillomavirus, hepatitis B virus; Plummer et al., ; Lunn et al., ), which have proven to be much more durable in the face of pathogen evolution than have treatments targeting established infections (Kennedy & Read, ). Established infections of oncogenic viruses should evolve to oppose our cancer therapies, but it is unclear how readily viruses could manipulate the cancer phenotype of their host's cells to evade our treatments; empirical work on this question is needed.…”
Section: Infectious and Pathogen‐associated Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis B virus (HBV) and hepatitis C virus (HCV) have been identified as oncogenic viruses that might cause non-Hodgkin's lymphomas (NHL) by the International Agency for Research on Cancer (IARC). 1 The association between HBV or HCV infection and NHL has been demonstrated in diverse epidemiological studies and mainly observed in B-cell non-Hodgkin's lymphoma (B-NHL). [2][3][4][5][6][7] Furthermore, it was reported in different interventional studies that patients with both HCV infection and indolent B-NHL such as splenic marginal zone lymphoma (SMZL), mucosa-associated lymphoid tissue lymphoma (MALT) and follicular lymphoma (FL) were successfully treated with anti-HCV agents such as (pegylated) interferon and ribavirin.…”
Section: Introductionmentioning
confidence: 99%
“…The x-axis is obtained by dividing the estimated number of cancer cases worldwide by the global prevalence. Data originates from [21]. [3].…”
Section: Introductionmentioning
confidence: 99%